Iceland : Report on the Observance of Standards and Codes; FATF Recommendations for Anti-Money Laundering and Combating the Financing of Terrorism. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2007)
This paper examines Iceland's Observance of Standards and Codes on the Financial Action Task Force Recommendations for Anti-Money Laundering and Combating the Financing of Terrorism. Iceland's legal requirements in place to combat money laundering and terrorist financing are generally comprehensive. The penalties for money laundering appear low, and the number of money laundering prosecutions and convictions has decreased. The terrorist financing offence is generally broad, although it does not fully cover the financing of acts listed in the Terrorist Financing Convention.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet